2019
DOI: 10.3390/atmos10120757
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal Changes in the Influence of the Arctic Oscillation on the East Asian Surface Air Temperature in Boreal Winter

Abstract: The time-varying influences of the wintertime Arctic Oscillation (AO) on the concurrent East Asian surface air temperature (EAT) are investigated based on JRA-55 reanalysis data. Results reveal that there are multidecadal variations in the influences of wintertime AO on the EAT during 1958–2018. Before the mid-1980s, the impact of winter AO on the simultaneous EAT is weak and confined northward of 40° N over East Asia. After the mid-1980s, by contrast, the winter AO’s influence is stronger and can extend south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The multi‐year regression shows the main features of winter‐early spring 2020: an extensive positive relation from Europe through East Asia and a bimodal maxima distribution over Europe and East Asia. Eurasian surface air temperature anomalies have also been shown to be associated with the persistence of large‐scale atmospheric circulation anomaly patterns over the North Atlantic and Eurasia, featuring a combination of the North Atlantic Oscillation (NAO)/AO and the Scandinavian pattern (SCA), from winter to spring (Gong et al ., 2019; Wu and Chen, 2020). NAO was greater than 1.0 for January–March 2020 and SCA was strongly negative (negative heights over Scandinavia and correlated with positive Siberian temperatures) for January–May 2020.…”
Section: Comparisons With Climatologymentioning
confidence: 99%
See 1 more Smart Citation
“…The multi‐year regression shows the main features of winter‐early spring 2020: an extensive positive relation from Europe through East Asia and a bimodal maxima distribution over Europe and East Asia. Eurasian surface air temperature anomalies have also been shown to be associated with the persistence of large‐scale atmospheric circulation anomaly patterns over the North Atlantic and Eurasia, featuring a combination of the North Atlantic Oscillation (NAO)/AO and the Scandinavian pattern (SCA), from winter to spring (Gong et al ., 2019; Wu and Chen, 2020). NAO was greater than 1.0 for January–March 2020 and SCA was strongly negative (negative heights over Scandinavia and correlated with positive Siberian temperatures) for January–May 2020.…”
Section: Comparisons With Climatologymentioning
confidence: 99%
“…The multi-year regression shows the main features of winterearly spring 2020: an extensive positive relation from Europe through East Asia and a bimodal maxima distribution over Europe and East Asia. Eurasian surface air temperature anomalies have also been shown to be (Gong et al, 2019;Wu and Chen, 2020). NAO was greater than 1.0 for January-March 2020 and SCA was strongly negative (negative heights over Scandinavia and correlated with positive Siberian temperatures) for January-May 2020.…”
Section: Comparisons With Climatologymentioning
confidence: 99%
“…Zhang et al (2019) also emphasized the important impacts of equatorial La Niña and mega-La Niña on the cold southern mode of winter East Asian SAT (EASAT). Some studies suggested that the Arctic Oscillation (AO)/Northern Hemisphere (NH) Annular Mode (NAM) could contribute to anomalously low SAT in the winter NH mid-latitudes as well as China (Gong et al, 2001;Wu and Wang, 2002;Jeong and Ho, 2005;Li, 2005a, b;Wang and Chen, 2010;Ha et al, 2012;Sun and Li, 2012;Chen et al, 2013;Ding et al, 2014;Yun et al, 2014;Zuo et al, 2015;Li, 2016;Li et al, 2019a) and the springtime extreme low temperature events in northeast China (Yin et al, 2013;Li, 2016). In addition, there are other responsible factors for the winter EASAT, e.g., the autumn and winter Arctic sea ice (Wu et al, 2011a(Wu et al, , 2011bLi and Wu, 2012;Li et al, 2019c;Zhang et al, 2020), autumnal North Pacific sea surface temperature (SST) (Kim and Ahn, 2012), two types of El Niño (Hu et al, 2012), Southern Hemisphere annular mode (SAM) (Wu et al, 2009(Wu et al, , 2015Zheng et al, 2014;Li, 2016), Eurasian snow cover (Yu et al, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The total column air mass, which is proportional to the surface pressure, shows positive (negative) anomalies in the high (mid‐) latitudes associated with WB_D + events (Figure 4c), suggesting a negative phase of the Arctic Oscillation. A negative Arctic Oscillation is well known to be accompanied by stronger planetary wave activity, favoring the stronger southward transport of cold air (Chen et al., 2005; Yu et al., 2015b; H. Gong et al., 2019a, 2019b). By contrast, a positive Arctic Oscillation, which corresponds to stronger westerly winds in the extratropics (Thompson & Wallace, 1998, 2000), accompanies WB_M + events, promoting the development of synoptic‐scale eddies (Thompson et al., 2003; Yamada & Pauluis, 2015) and the supply of water vapor to the poleward moist component of the warm branch.…”
Section: Why Does the Wb_d Have A Closer Relationship With Mid‐latitumentioning
confidence: 99%
“…The total column air mass, which is proportional to the surface pressure, shows positive (negative) anomalies in the high (mid-) latitudes associated with WB_D + events (Figure 4c), suggesting a negative phase of the Arctic Oscillation. A negative Arctic Oscillation is well known to be accompanied by stronger planetary wave activity, favoring the stronger southward transport of cold air (Chen et al, 2005;Yu et al, 2015b;H. Gong et al, 2019aH.…”
Section: Why Does the Wb_d Have A Closer Relationship With Mid-latitude Surface Cooling?mentioning
confidence: 99%